Quantification of the geometric uncertainty when using implanted markers as a surrogate for lung tumor motion. Issue 6 (14th May 2021) - Hardcastle, Nicholas; Briggs, Adam; Caillet, Vincent; Angelis, Giorgios; Chrystall, Danielle; Jayamanne, Dasantha; Shepherd, Meegan; Harris, Ben; Haddad, Carol; Eade, Thomas; Keall, Paul; Booth, Jeremy
Abstract : Background: Fiducial markers are used as surrogates for tumor location during radiation therapy treatment. Developments in lung fiducial marker and implantation technology have provided a means to insert markers endobronchially for tracking of lung tumors. This study quantifies the surrogacy uncertainty (SU) when using endobronchially implanted markers as a surrogate for lung tumor position. Methods: We evaluated SU for 17 patients treated in a prospective electromagnetic‐guided MLC tracking trial. Tumor and markers were segmented on all phases of treatment planning 4DCTs and all frames of pretreatment kilovoltage fluoroscopy acquired from lateral and frontal views. The difference in tumor and marker position relative to end‐exhale position was calculated as the SU for both imaging methods and the distributions of uncertainties analyzed. Results: The mean (range) tumor motion amplitude in the 4DCT scan was 5.9 mm (1.7–11.7 mm) in the superior–inferior (SI) direction, 2.2 mm (0.9–5.5 mm) in the left–right (LR) direction, and 3.9 mm (1.2–12.9 mm) in the anterior–posterior (AP) direction. Population‐based analysis indicated symmetric SU centered close to 0 mm, with maximum 5th/95th percentile values over all axes of −2.0 mm/2.1 mm with 4DCT, and −2.3/1.3 mm for fluoroscopy. There was poor correlation between the SU measured with 4DCT and that measured with fluoroscopy on a per‐patient basis. We observed increasing SU with increasing surrogate motion. Based on fluoroscopy analysis, the mean (95% CI) SU was 5% (2%–8%) of the motion magnitude in the SI direction, 16% (6%–26%) of the motion magnitude in the LR direction, and 33% (23%–42%) of the motion magnitude in the AP direction. There was no dependence of SU on marker distance from the tumor. Conclusion: We have quantified SU due to use of implanted markers as surrogates for lung tumor motion. Population 95th percentile range are up to 2.3 mm, indicating the approximate contribution of SU to total geometric uncertainty. SU was relatively small compared with the SI motion, but substantial compared with LR and AP motion. Due to uncertainty in estimations of patient‐specific SU, it is recommended that population‐based margins are used to account for this component of the total geometric uncertainty.